THE EVALUTION OF THE CHANGEABLE EDUCATIONAL ENVIRONMENT OF LATVIA RURAL SCHOOLS - Katane, Irena; Jurgena, Inese; Laizane, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nowadays Latvian rural schools function under the conditions of constantly changeable environment, where the process of self-development is observed. Due to the influence of economical, demographical and social crises the problem of the sustainability of a rural school as the educational environment has become urgent in Latvia. The sustainability of rural community and its cultural environment also considerably depends on the sustainability of a rural school. The educational environment of rural schools has been studied by the authors of this article for many years, providing the multi-dimensional point of view. The research results enable to draw a conclusion that very important changes have taken place in the educational environment of research base schools. In outcome rural school of general education becomes a multi-level, multi-component and multi-functional educational environment in the countryside of Latvia that strives by help of education to promote the development of the pupil as a personality as well as the development of the local rural community.